UJI AKTIVITAS ANTI BAKTERI EKSTRAK ETANOLIK UMBI AKAR BATU (Coccinia grandis L.Voight) TERHADAP BAKTERI SALMONELLA SP - Rukmana, Rizal Maarif; Nugroho, Rahmat Budi; Wisnumurti, Dwi Admani (Bioeksperimen: Jurnal Penelitian Biologi, 2020)
AbstractSalmonella sp are bacteria that often infect human and animal. This type of bacteria can cause Salmonellosis in human. Previous research has been carried out on secondary metabolites of plants as medicinal ingredients. One of the plants that has potential as a medicine is stone Akar Batu (Coccinia grandis L Voight). This study aims at examining the antibacterial activities of ethanolic extract of stone Akar Batu on Salmonella sp. The extraction method was carried out by maceration and the solvent used was ethanol 96%. Antibacterial activity was conducted using diffusion method. Identification of compound groups of extracts was done by reacting extracts with various chemical reagents. The results showed that stone of Akar Batu powder had a moisture content of 5.99% and a yield of 1.76%. The identification results of ethanolic extract of stone Akar Batu chemical group indicated that the extract contained flavonoids, alkaloids, saponins and tannins. The results of antibacterial activity test have revealed that ethanolic extract of stone Akar Batu can inhibit Salmonella sp.